2009
DOI: 10.1002/ejic.200900115
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride‐Free Hiyama and Copper‐ and Amine‐Free Sonogashira Coupling in Air in a Mixed Aqueous Medium by a Series of PEPPSI‐Themed Precatalysts

Abstract: A new series of robust, user‐friendly, and highly active PEPPSI‐themed (pyridine‐enhanced precatalyst preparation, stabilization and initiation) (NHC)PdX2(pyridine)‐type (X = Cl, Br) precatalysts of C4–C5 saturated imidazole‐ (1–4) and triazole‐based (5 and 6) N‐heterocyclic carbenes for the Hiyama and Sonogashira couplings under amenable conditions are reported. Specifically 1–6 efficiently catalyze the fluoride‐free Hiyama coupling of aryl halides with PhSi(OMe)3 and CH2=CHSi(OMe)3 in air in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 70 publications
(33 reference statements)
7
53
0
Order By: Relevance
“…Under standard reaction conditions reported in the literature, 21 an isolated yield of 27% diphenylacetylene product suggests that the Sonogashira coupling does not benefit from the steric demand of the IPr** system. Scheme 3.…”
Section: Catalytic Applicabilitymentioning
confidence: 89%
“…Under standard reaction conditions reported in the literature, 21 an isolated yield of 27% diphenylacetylene product suggests that the Sonogashira coupling does not benefit from the steric demand of the IPr** system. Scheme 3.…”
Section: Catalytic Applicabilitymentioning
confidence: 89%
“…151.3-152.5 ppm for these complexes. The resonance of carbene carbon in these C4-C5 unsaturated palladium complexes is significantly upfield compared to that in those C4-C5 saturated complexes (184.2-186.3 ppm) [22], which means that the carbene in unsaturated complexes is more electron rich than that in their saturated analogues. The 1 H NMR of complex 2 showed that only one signals for six of CH 3 of t-butyl group and the 1 H NMR patterns of four CH 3 groups of 1,6-substituents on phenyl 14 ppm for 4) as well.…”
mentioning
confidence: 97%
“…[8] Thus, we synthesized different types of Pd-NHC-Py complexes 1-3 (Scheme 1) according to a literature procedure [9] and investigated their catalytic activities in the α-ketone arylation of aryl halides. To understand whether the supporting pyridine ligand affects the catalytic activity in the reaction, we also tested its 3-chloropyridine analogue 4, which is commercially available.…”
Section: Resultsmentioning
confidence: 99%